Long-Term Stability in Temporomandibular Joint Replacement: A Review of Related Variables - Erick Vargas; Victor Ravelo; Majeed Rana; Alejandro Unibazo; Sergio Olate (MDPI AG, 2024)
Background: The temporomandibular joint (TMJ) is a key component of the stomatognathic system, playing a major role in maintaining mandibular stability and function. Temporomandibular disorders (TMDs) are a prevalent disease in the world, with surgical treatment being reserved for complex cases or end-stage TMJ disease. A narrative review was conducted to describe the quantitative and qualitative factors that affect TMJ prosthesis stability. Methods: Studies with a sample size equal to or greater than 10 subjects who underwent surgical procedures for joint replacement using stock or customized ATM prostheses were included. This narrative review examined some variables that may influence in terms of the longevity of the TMJ prosthesis, highlighting issues to be considered in future research. Results: The current development of TMJ prostheses is benefiting from technological advances, offering a suitable adaptation to the patient's anatomy and superior results in functionality and patient satisfaction. However, the biomechanical complexity of the TMJ shows unique challenges compared to other joints in the body, where anatomical, biomechanical, and functional requirements are high. The stability of the TMJ prosthesis is affected by multiple variables, including the selection of biocompatible materials that resist corrosion and wear, the design of the prosthesis, the diagnosis and indication for its use, and the surgeon's experience. The success of TMJ replacement can be measured by improving the patient's quality of life, reducing pain, restoring mandibular functionality, and recovering suitable facial morphology for the patient's conditions. Conclusion: There is a need for training of maxillofacial surgeons in TMJ surgery and replacement, as well as a greater focus on the research and development of systems to simplify surgical design and procedures and to optimize the results of TMJ replacement.